Ответы 1

  • 2(3 - b) + 5(b - 3)² = 6 - 2b + 5(b² - 6b +9) = 6 - 2b + 5b² - 30b + 45 =                            = 5b² - 32b +51          D = 1024 - 1020 = 4                                                            b₁ = (-b + √D)/2a = (32 + 2)/10 = 3,4                                                            b₂ = (-b - √D)/2a = (32 - 2)/10 = 35b² - 32b +51 = 5(b - 3,4)(b - 3) = (5b - 17)(b - 3)
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years